PENGARUH INDEPENDENSI, CORPORATE GOVERNANCE, UKURAN PERUSAHAAN DAN KUALITAS AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2014) - Lutfi Nihayatul Husna, 12.05.52.0021; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2016)
The research aims to analyze the influence of independence, Institusional Ownership, Independent Commissioner, audit committee, Firm Size and Audit Quality toward Integrity of financial Statements on Manufacture that Listed in Indonesia Stock Exchange Periode 2012-2014.Â The population in this research was all companies manufacture that listed in Indonesia Stock Exchange Period 2012-2014. Selection of sample used purposive sampling method. The analysis used in this research are multiple linier regression model.Â The result showed that the F-test statistic shows that, between independence, Institusional Ownership, Independent Commissioner, audit committee, Firm Size and Audit Quality jointly influence toward Integrity of financial Statements. And the results of the testing of hypotheses partial evaluation shows Institusional Ownership, audit committee, Firm Size that there is a positive significant toward Integrity of financial Statements. While for independence, Independent Commissioner, there is a negative not significant toward Integrity of financial Statements. While for Audit Quality there is a negative significant toward Integrity of financial Statements.Keywords: Integrity Of Financial Statement, Independence, Institusional Ownership, Independent Commissioner, Audit Committee, Firm Size, Audit Quality